Pozycja geopolityczna Chin w ujęciu potęgometrycznym - Krzysztof Surowiec (Przegląd Geopolityczny)
After the end of the Cold War, the geopolitical situation in the world began to change rapidly. The decline in Russia's importance enabled the U.S. to achieve world supremacy for two decades, but since the beginning of the 21st century there has also been a very rapid rise in China's power. The purpose of the article is to explain the reasons for the country's growth in recent decades, based on analyses of its geopolitical position, as determined by synthetic measures of power, particularly by the Mirosław Sułek model, as well as available rankings. China's position calculated on the basis of synthetic measures indicated that China, in all categories of power in the 21st century, ranked first or second in the world. No other country has achieved such a position in the 21st century except the US and China. It is worth noting that in terms of economic/general power, Beijing has already surpassed Washington in 2017. In the other models presented for the 2019-23 power categories, China also ranked very high. In contrast, the selected rankings present an overall low position of the Middle Kingdom.